IMPLEMENTATION OF THE FORMATION OF GOVERNMENT REGULATION NUMBER 66 OF 2015 CONCERNING MUSEUMS TOWARDS THE BANK INDONESIA MUSEUM - Rumani Hastuti; Uyan Wiryadi; Teguh Satya Bhakti (JILPR Journal Indonesia Law and Policy Review, 2026)
Museums play a strategic role as institutions that not only store but also preserve and communicate cultural, historical, and scientific heritage to the public. Government Regulation Number 66 of 2015 concerning Museums affirms the museum's function to protect, develop, utilize collections, and convey them to the public. However, in practice, the implementation of this regulation does not always align with the established ideal standards. The Bank Indonesia Museum, as the case study for this research, occupies a crucial position because it not only houses national banking history collections but also falls under a monetary authority distinct from the typical museum management model. Method In this study, the type of research used is normative legal research/normative juridical legal research. This research was conducted to identify the implementation of the formation of Government Regulation Number 66 of 2015 concerning Museums in the management and utilization of the Bank Indonesia Museum. The research results indicate that the implementation of Government Regulation No. 66 of 2015 concerning Museums in the management and utilization of the Bank Indonesia Museum has been realized through institutional strengthening, standardized collection management, improved human resource quality, and optimization of educational, research, and recreational functions. The implementation of Government Regulation No. 66 of 2015 concerning Museums in the management and utilization of the Bank Indonesia Museum still faces several obstacles.